Formulation and Antibacterial Activity Test of Peel-Off Gel Mask Ethyl Acetate Fraction of Cocoa Pods (Theobroma cacao L.) against Staphylococcus aureus as Anti-Acne - Immanuela Irene Mandias; Paulina Yamlean; Surya Sumantri Abdullah (UNIVERSITAS SAM RATULANGI, 2022)
Cocoa pods (Theobroma cacao L.) is a part of the Cocoa plant which contains active compounds such as flavonoids, alkaloids, saponins and tannins that have the potential as antibacterial. This study aimed to formulate a peel-off gel mask preparation of the ethyl acetate fraction which is physically good and to test the inhibitory power of the peel-off gel mask with concentrations of 2, 4, 8, 10, and 12% against Staphylococcus aureus. This research used laboratory experimental method. The results showed that the peel-off gel mask filled the requirements for physical evaluation, that is organoleptic, homogeneity, pH, spreadability, adhesion and drying time. The antibacterial activity test using the well diffusion method showed that the average diameter for F1 to F5 respectively was 7,5; 8,58; 12; 12,75; and 14 mm. Based on the result of the study it can be included that the overall formulation of the peel-off gel mask filled the requirements of the parameters of the physical properties of the preparation and provides the greatest antibacterial activity that is formula 5 with a concentration of 12%, which is 14 mm.